STUDENT PERSPECTIVES ON INTEGRATED LEARNING: THE ROLES OF CLIL AND LEXICAL INSTRUCTION IN FOOD TECHNOLOGY ESP STUDENTS - Djabbarova Dilfuza Gayratovna (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This research explores the usefulness of Content and Language Integrated Learning (CLIL) combined with obvious lexical instruction among Food Technology students enrolled in English for Specific Purposes (ESP) courses. As the food industry becomes increasingly globalized, students require both technical mastery and high-level linguistic competence. This study utilizes a mixed-methods approach to evaluate how students perceive the integration of content-driven lessons and systematic vocabulary achievement. Results indicate that while CLIL enhances motivation and professional contextualization, explicit lexical instruction is perceived as the essential bridge that allows students to navigate complex scientific texts. The findings suggest that a hybrid pedagogical model is superior to isolated language or content teaching.